Functional capabilities of bacterial biofilms on gold particles. Issue 1 (6th December 2019) - Reith, Frank; Falconer, Donna M; Van Nostrand, Joy; Craw, David; Shuster, Jeremiah; Wakelin, Steven
ABSTRACT: Gold particles contain gold and other toxic, heavy metals, making them 'extreme' geochemical microenvironments. To date, the functional capabilities of bacterial biofilms to deal with these conditions have been inferred from taxonomic analyses. The aims of this study are to evaluate the functional capabilities of bacterial communities on gold particles from six key locations using GeoChip 5.0 and to link functional and taxonomic data. Biofilm communities displayed a wide range of functional capabilities, with up to 53 505 gene probes detected. The capability of bacterial communities to (re)cycle carbon, nitrogen, and sulphur were detected. The cycling of major nutrients is important for maintaining the biofilm community as well as enabling the biogeochemical cycling and mobilisation of heavy and noble metals. Additionally, a multitude of stress- and heavy metal resistance capabilities were also detected, most notably from the α/β/γ-Proteobacteria and Actinobacteria. The multi-copper-oxidase gene cop A, which is directly involved in gold resistance and biomineralisation, was the 15th most intense response and was detected in 246 genera. The Parker Road and Belle Brooke sites were consistently the most different from other sites, which may be a result of local physicochemical conditions (extreme nutrient poverty and sulphur-richness, respectively). In conclusion, biofilms on gold particles display wide-ranging metabolic and stress-related capabilities, which may enable them to survive in these niche environments and drive biotransformation of gold particles. Abstract : In this paper functional and taxonomic data are linked to assess how bacterial biofilms can thrive on natural, toxic gold particle surfaces and here drive particle transformation and gold cycling.